If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 107 = -4 + 3(1 + 6n) 107 = -4 + (1 * 3 + 6n * 3) 107 = -4 + (3 + 18n) Combine like terms: -4 + 3 = -1 107 = -1 + 18n Solving 107 = -1 + 18n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-18n' to each side of the equation. 107 + -18n = -1 + 18n + -18n Combine like terms: 18n + -18n = 0 107 + -18n = -1 + 0 107 + -18n = -1 Add '-107' to each side of the equation. 107 + -107 + -18n = -1 + -107 Combine like terms: 107 + -107 = 0 0 + -18n = -1 + -107 -18n = -1 + -107 Combine like terms: -1 + -107 = -108 -18n = -108 Divide each side by '-18'. n = 6 Simplifying n = 6
| x*2+y*3=24 | | 5.4-3.1(4n+3)=45.7 | | 222=-6(7x-3)-6 | | K-11=2 | | 7Y+3=Y | | (7Y+3)+(3Y+4)=14y-25 | | d+e+e+e+d+d+d+d= | | 218=5a+8(1-5a) | | 72+1x=160 | | 3(3x-4)-8= | | 14y-7=7y | | 4x-7y=-21 | | 14y-6y=56 | | m+3+2m+1=5m+3 | | 0=1.2+4.9*t | | m/3-8=-1 | | -153=9m+9 | | 14=a-5.5 | | -x+3+4-x-2+x=-x+2-3 | | b+b+b+b+c+c+c= | | 7g-9=5f+5 | | -4(7+2x)+4=-88 | | x-8=4x-13 | | 3(x+4)-(x-5)=3(x+3) | | 16x^2+25x=4 | | (99-2x)=8x | | -(x+4)-2=8-(x-3) | | 10-(2x+1)=3x+4 | | 46=6+5x | | 70=-2(-8+5) | | 8h=14-6h | | 3(5-2h)+9=-90 |